Dissociative Disorders: Between Neurosis and Psychosis - Devillé, C.; Moeglin, C.; Sentissi, O. (Case Reports in Psychiatry, 2014)
Dissociative disorders are a set of disorders defined by a disturbance affecting functions that are normally integrated with a prevalence of 2.4 percent in industrialised countries. These disorders are often poorly diagnosed or misdiagnosed because of sharing common clinical features with psychotic disorders, but requiring a very different trajectory of care. Repeated clinical situations in a crisis centre in Geneva provided us with a critical overview of current evidence of knowledge in clinical and etiopathological field about dissociative disorders. Because of their multiple expressions and the overlap with psychotic disorders, we focused on the clinical aspects using three different situations to better understand their specificity and to extend our thinking to the relevance of terms “neurosis” and “psychosis.” Finally, we hope that this work might help physicians and psychiatrists to become more aware of this complex set of disorders while making a diagnosis.